PROSEDUR PENYEBARAN RISIKO ASURANSI KEBAKARAN DALAM REASURANSI TREATY PROPORSIONAL, STUDY KASUS PT. TUGU PRATAMA INDONESIA. - Kuncoro Kuncoro (Jurnal Vokasi Indonesia, 2014)
Understanding the principles of insurance professionally are an important things for those insurer,  in return for the payment of a premium, promises to pay an amount of money on the occurrence  of a defined events. By doing so this enables an individual to protect themselves against the financial effects of certain event or events.